Докажите тождество:
1) $(4a^2 + 3)^2 + (7 - 4a^2)^2 - 2(4a^2 + 3)(4a^2 - 7) = 100$;
2) $(a^2 - 6ab + 9b^2)(a^2 + 6ab + 9b^2) - (a^2 - 9b^2)^2 = 0$.
$(4a^2 + 3)^2 + (7 - 4a^2)^2 - 2(4a^2 + 3)(4a^2 - 7) = 100$
$16a^4 + 24a^2 + 9 + 49 - 56a^2 + 16a^4 - 2(16a^4 + 12a^2 - 28a^2 - 21) = 100$
$32a^4 - 32a^2 + 58 - 2(16a^4 - 16a^2 - 21) = 100$
$32a^4 - 32a^2 + 58 - 32a^4 + 32a^2 + 42 = 100$
58 + 42 = 100
100 = 100
$(a^2 - 6ab + 9b^2)(a^2 + 6ab + 9b^2) - (a^2 - 9b^2)^2 = 0$
$(a - 3b^2)^2(a + 3b^2)^2 - (a^2 - 9b^2)^2 = 0$
$(a^2 - 9b^2)^2 - (a^2 - 9b^2)^2 = 0$
0 = 0
Пожауйста, оцените решение